Synovial cells responding to a 65-kDa mycobacterial heat shock protein have a high proportion of a TcR gamma delta subtype uncommon in peripheral blood. - Söderström, K; Halapi, E; Nilsson, E; Grönberg, A; van Embden, J; Klareskog, L; Kiessling, R (1990)
We have analysed the ability of T cells from synovial fluid mononuclear cells (SFMC) and from peripheral blood mononuclear cells (PBMC) of inflammatory arthritic diseases to proliferate in response to mycobacterial antigens (65-kDa heat shock protein [hsp] of BCG, whole BCG) and to rat collagen type II. The SFMC demonstrated a significantly greater ability to respond to 65-kDa hsp of BCG, and to whole BCG, compared with PBMC from the same patients. With collagen type II, only a small proportion of the patients showed a proliferative response, although with this antigen also SFMC responded better than PBMC. There was no difference between SFMC and PBMC in the response to control antigen (tetanus toxoid), phytohaemagglutinin (PHA), or interleukin 2 (IL-2). A high proportion of cells in SFMC-derived short-term T-cell lines were of TcR gamma delta type, often exceeding the number of TcR gamma beta type. There was a significantly higher proportion of TcR gamma delta cells in the SFMC lines compared with the PBMC lines, and a large part of the TcR gamma delta cells in the SFMC cultures was CD8+. The SFMC lines had a high proportion of delta-TCS-1+ cells (V delta 1) among their TcR gamma delta cells, always exceeding the percentages of Ti gamma A+(V gamma 9) and BB3+ (V delta 2). In the PBMC lines, the distribution of TcR gamma delta subtypes was markedly different, with a Ti gamma A+/BB3+ population in the majority. These data argue for a different subpopulation distribution of TcR gamma delta cells in synovial fluid compared with peripheral blood of patients with inflammatory arthritic diseases.